Soluble Receptor for Advanced Glycation End Product Is Involved in the Inflammatory Response of Human Adenovirus-Infected Patients - Xu, Wen; Wu, Cheng-Jun; Jiao, Yan-Mei; Mei, Xiao-Le; Huang, Lei; Qin, En-Qiang; Tu, Bo; Zhao, Peng; Wang, Li-Feng; Chen, Wei-Wei (Frontiers in Microbiology, 2022)
Human adenovirus (HAdV) infection causes excessive inflammation associated with severe tissue injury, such as pneumonia. The molecules involved in the underlying inflammatory mechanisms remain to be elucidated. Receptor for advanced glycation end product (RAGE) is mainly expressed on immune cells and lung tissues, and it is a key factor in the initiation and development of inflammation. RAGE can be cleaved by metalloprotease MMP9 to release the extracellular segment, which is named soluble RAGE (sRAGE), into the intercellular space, where it can bind to RAGE ligands and block RAGE activation and subsequent inflammation. In our study, we enrolled HAdV-infected patients and their contacts to examine the relationship between sRAGE and inflammation induced by HAdV infection. The results showed that HAdV infection stimulated inflammatory cytokine secretion, increased HMGB1 levels and suppressed sRAGE expression. sRAGE levels were significantly different between patients with or without pneumonia. We also found that MMP9 was significantly lower in patients with pneumonia, and it was positively correlated with sRAGE levels over 7 days after disease onset. The MAPK pathway is an important immune activation signaling pathway that is regulated by RAGE. We observed activation of the MAPK pathway in the PBMCs of patients. Negative correlations between sRAGE and phosphorylated JNK and p38 were observed. These results suggest that sRAGE is involved in HAdV induced inflammatory responses and might be a potential therapeutic target to alleviate HAdV induced excessive inflammation.